2018
DOI: 10.1177/1747021817744546
|View full text |Cite
|
Sign up to set email alerts
|

Biasing and debiasing health decisions with bar graphs: Costs and benefits of graph literacy

Abstract: Bar graphs can improve risk communication in medicine and health. Unfortunately, recent research has revealed that bar graphs are associated with a robust bias that can lead to systematic judgment and decision making errors. When people view bar graphs representing means they tend to believe that data points located within bars are more likely to be part of the underlying distributions than equidistant points outside bars. In three experiments we investigated potential consequences, key cognitive mechanisms, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 44 publications
0
34
0
Order By: Relevance
“…When reading barplots, people tend to believe that points within the bar are more likely than outside the bar – even if they are equidistant relative to the top of the bar (Newman and Scholl, ; Okan et al . ). FeWIS Pro's barplots (Figure d) factor this tendency in by displaying the 90%ile as the full height of the stacked bars, which implies that values outside the bar are in fact less likely than those within the bar.…”
Section: Three Diverse Practical Applicationsmentioning
confidence: 97%
“…When reading barplots, people tend to believe that points within the bar are more likely than outside the bar – even if they are equidistant relative to the top of the bar (Newman and Scholl, ; Okan et al . ). FeWIS Pro's barplots (Figure d) factor this tendency in by displaying the 90%ile as the full height of the stacked bars, which implies that values outside the bar are in fact less likely than those within the bar.…”
Section: Three Diverse Practical Applicationsmentioning
confidence: 97%
“…23 More graphliterate individuals also benefit more from interventions designed to improve risk understanding or to reduce errors and biases in graph comprehension (e.g., benefit from error bars). 21,27 Despite its success, like all scales, the OGL scale has some limitations. One of the more pressing issues is that it typically requires 9 to 17 minutes to complete, 10,16,25 which may be too long for some uses (e.g., in clinical practice).…”
mentioning
confidence: 99%
“…Newman and Scholl (2012) demonstrated that the use of bar charts to present means leads to a within-the-bar bias such that values within the bar are perceived as more likely than values outside (e.g., above) the bar (see also Fritz, Morris, Cherchar, Smith, & Roe, 2015;Okan, Garcia-Retamero, Cokely, & Maldonado, 2017).…”
mentioning
confidence: 99%